2007
DOI: 10.1111/j.1399-302x.2007.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome hybridization of Streptococcus mutans strains

Abstract: The basis for genotypic and phenotypic variation within Streptococcus mutans is poorly understood but the availability of the genome sequence of strain UA159 provides an opportunity for comparative studies. Genomic DNA prepared from nine strains of S. mutans was used to probe a microarray consisting of oligonucleotides representing 1948 open reading frames of S. mutans UA159. A total of 385 (20%) of the UA159 open reading frames were found to be absent from one or more of the test strains. Absent open reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…We found that genes within three different genomic islands were differentially regulated in the clpP mutant (Table 1). Among them were two genomic islands, TnSmu1 and TnSmu2, whose distribution among the different isolates had been previously studied (50,51). TnSmu1 corresponds to a large region of 23 kb spanning from SMU.191 to SMU.226 (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…We found that genes within three different genomic islands were differentially regulated in the clpP mutant (Table 1). Among them were two genomic islands, TnSmu1 and TnSmu2, whose distribution among the different isolates had been previously studied (50,51). TnSmu1 corresponds to a large region of 23 kb spanning from SMU.191 to SMU.226 (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…They constitute the dispensable genome, while those genes shared by all strains within a species are regarded as the core genome. In S. mutans, comparison of the genome sequences of strains UA159 and NN2025 revealed that these two strains differ in 10% of the genes (47), while 20% of the open reading frames (ORFs) in strain UA159 have been estimated to belong to the dispensable genome by a DNA hybridization-based comparison with nine other strains (83). In addition, comparative genome hybridization of 11 strains showed that 16.6% of the ORFs included in the microarray were missing in at least one of the genomes (89).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, irvA induction has also been found to be associated with several other genetic mutations known to have multiple stress-and virulence-related phenotypes (40). Moreover, irvA has thus far been detected in numerous strains of S. mutans (1,25,42); therefore, it may be a fundamental component of the basic machinery utilized to modulate multiple virulence-associated functions required for persistence.…”
mentioning
confidence: 99%